Niphargus (Crustacea: Amphipoda) species in Hungary: literature review, current taxonomy and the updated distribution of valid taxa - Balázs, Gergely; Angyal, Dorottya; Kondorosy, Előd (Zootaxa, 2015)
Research of the Hungarian Niphargus species is a rather neglected field. This is due to the growing distance between the  level of knowledge about Hungarian species and the elaboration determined by the international publications, which had caused a hardly negotiable inconvenience in the judgment of the state of the Hungarian species. The clarification of species in questionable positions could be the starting point of further inland research. During our work, the species with Hungarian distributions were assigned based on the literature’s data, and were evaluated with morphological examinations of the specimens collected by us from their type localities and other habitats. Considering the validity of the species we created three categories. Eight of the 20 species proved to be invalid or non-inland species, three remain in an uncertain taxonomic state, while nine are classifiable into the ’valid Hungarian species’ category. During the 43 samplings in 27 localities we added new distributional data for seven species.